Coronamyia, a new genus of Neotropical Maruinini (Diptera, Psychodidae) with the description of four new species - Bravo, Freddy; Lopes, Priscila Silva; Araújo, Maíra Xavier (Zootaxa, 2023)
Coronamyia gen. nov., a new Neotropical genus of Psychodidae with records restricted to northeastern and southeastern Brazil is described, as well as four new species: C. paschoali sp. nov., C. santosi sp. nov., C. triangularis sp. nov., and C. trilobata sp. nov. The new genus is morphologically similar to Alepia Enderlein, 1937, but can be differentiated by the presence of a lightly sclerotized plate with long thin setae around the aedeagus, which is absent in Alepia. Coronamyia biapicalis comb. nov. is transferred from Alepia.